Man and artist searching for identity. Victor Ciutac, actor – 80 years from birth (Confluenţe Bibliologice, 2017)
The article presents sequences from the life and the theatrical and cinematographic work of the great artist Victor Ciutac, who would have celebrated his 80th anniversary. The librarian dedicated an online exhibition "I would like to have a name and an address ..." Victor Ciutac – 80 years from birth (12 January 1938 - 18 January 2009).
Keywords: Ciutac Victor (1938); anniversary exhibition; theater and ﬁlm actors